Predicting beef carcass retail yield from hot carcass traits - Apple, J.K.; Cundiff, L.V.; Wise, J.W.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Hot carcasses from 288 steers were used to develop equations to predict weights and percentages of trimmed retail cuts. and trimmable fat yields from hot carcass traits. Independent variables examined were: (1) 12-13th rib fat probe; (2) lO-11th rib fat probe; (3) external fat score; (4) percent kidney knob; (5) hindquarter muscling score, and (6) carcass weight. Right sides of carcasses were fabricated into boneless cuts trimmed to .3 in. fat and weighed. Then. cuts were totally trimmed (.0 in.) and reweighed. Multiple regression equations developed from these variables accounted for 95 and 90% of the variation in total weight of retail cuts at .3 and .0 in. trim levels. respectively. Furthermore, equations accounted for 58 and 52% of the variation in percent yield of trimmed retail cuts at .3 and 0 in. trim levels. respectively. Equations developed for trimmable fat accounted for 74 to 76% of the variation in pounds and percentages at both trim levels. Our "hot carcass" equations were equivalent to USDA equations that are based on chilled, ribbed-carcass traits in their ability to predict yields of trimmed retail cuts and trimmable fat.
Keywords: Beef; Hot beef carcass; Fat probe; External fat score; Retail yield; Regression equations; Carcass traits